2007
DOI: 10.1001/archneur.64.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis and Prenatal Prediction of Spinal Muscular Atrophy in Chinese Patients by the Combination of Restriction Fragment Length Polymorphism Analysis, Denaturing High-Performance Liquid Chromatography, and Linkage Analysis

Abstract: Background: The difficulties and incurability of spinal muscular atrophy (SMA) highlight the importance of prenatal diagnosis in families with SMA. However, the system applied in prenatal screening is far from perfect. Objectives: To optimize the molecular assays and establish a relatively perfect system for prenatal screening. Design, Setting, and Patients: A total of 87 patients and 132 parents from 77 families with SMA were screened for SMN1 mutations. Prenatal prediction was performed for 11 fetuses from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It was observed that the majority of patients with more SMN1 gene deletions resulted in a severe phenotype. Our results of exon 7 deletion were consistent with the studies from Taiwan, Hong Kong, and Fujian Province, China (Chang et al, 1995;Tsai et al, 2001;Wong and Chan, 2001;Su et al, 2005;Chen W.J. et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was observed that the majority of patients with more SMN1 gene deletions resulted in a severe phenotype. Our results of exon 7 deletion were consistent with the studies from Taiwan, Hong Kong, and Fujian Province, China (Chang et al, 1995;Tsai et al, 2001;Wong and Chan, 2001;Su et al, 2005;Chen W.J. et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The genomic complexity of the SMN region and its high degree of variability hamper the ability to directly screen the SMA carriers. Thus the comprehensive SMA tests including SMA deletion analysis, linkage analysis, and SMA heterozygosity detection should be the most complete evaluation of the clinical diagnosis or suspicion of SMA (Chan et al, 2004;Dastur et al, 2006;Chen W.J. et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR-RFLP was applied for screening the homozygous deletion of SMN gene as our previous report [35]. In brief, the exon 7/8 and flanking areas of the SMN1 and SMN2 genes were amplified by PCR with the primers of exon 7 (forward 5′-AGACTATCAACTTAATTTCTGATCA-3′, reverse 5′-CCTTCCTTCTTTTTGATTTTGTTT-3′) and exon 8 (forward 5′-TAATAACCAAATGCAATGTGAA-3′, reverse 5′-CTACAACACCCTTCTCACAG-3′).…”
Section: Methodsmentioning
confidence: 99%
“…20,22,23 We also assessed the genotype contribution of SMA carriers in the Chinese population by comparative genotyping of newborn samples and SMA core families. In addition, during the analysis of SMA patients, we found a novel SMN1 splice-site mutation at the junction between intron 6 and exon 7 (c.835-1G4A).…”
Section: Introductionmentioning
confidence: 99%